PENEGAKAN HUKUM PIDANA TERHADAP PELAKU PENAMBANG PASIR TANPA IJIN DI WILAYAH HUKUM POLRES KENDAL - Ikka Puspitasari; Eka P; Sitta Saraya (Journal Legal Dialectics, 2022)
ABSTRACT Sand mining without a permit is one of the mining business activities carried out without a people's mining permit (IPR) and a mining business permit (IUP). Many people in Kendal Regency use sand mining, both legally through permits and illegally to meet their economic needs. Law enforcement against unlicensed sand mining actors aims to determine the factors that cause sand mining activities without a permit and to find out the implementation of criminal law enforcement against unlicensed sand miners in order to enforce or function real legal norms and to find out the impact on surrounding environment. The research uses sociological juridical law research methods. Law enforcement in Kendal Regency based on Law No. 22 of 2011 concerning Mineral and Coal Mining authorizes enforcers in this case the police, prosecutors and courts with a maximum imprisonment of 3 (three) months and a maximum fine of Rp. 50,000,000.. Obstacles in law enforcement against the crime of illegal sand mining, namely geographical constraints, community economic problems, and low education problems